Voice of justice : reclaiming the First Amendment rights of lawyers - Tarkington, Margaret C., 1976- (Cambridge : Cambridge University Press, 2018)
The First Amendment rights of lawyers are ethereal. Most lawyers fail to realize that courts may deny them access to the First Amendment's protective shield in many regulatory and disciplinary contexts. Overall, attorneys cannot and should not assume that they can obtain First Amendment protection - especially when acting as an attorney in their role as an'officer of the court'. Yet, it is precisely in the lawyering context - where attorneys engage in speech, association, and petitioning for the very purpose of securing client rights, invoking law, enabling the judicial power, and obtaining justice - that the need for First Amendment protection is the most acute. If regulators silence that voice, they silence justice. From overarching theory to specific real-world contexts, this illuminating book provides a critical resource for lawyers, judges, and scholars to understand the relationship between the First Amendment rights of lawyers and the integrity of the justice system.
Do lawyers have First Amendment rights? -- Speech is all we have -- Self-regulation : myth and reality -- Attorneys as officers of the court and delegates of state power -- Core ideals of the First Amendment -- Cognate inseparable rights -- The access to justice theory -- Freedom to form an attorney-client relationship -- Safeguarding client counseling and confidences -- Invoking law and processes to protect client interests -- Safeguarding and impugning judicial integrity -- Securing criminal constitutional processes -- Uncompromised pretrial publicity -- Attorney civility, harassment, and discrimination.
Title from publisher's bibliographic system (viewed on 14 Sep 2018).
Keywords: Lawyers -- United States; Legal ethics -- United States; Practice of law -- United States; Attorney and client -- United States; Freedom of speech -- United States; United States